Allocation of post-consumer useless and usable tires: two case study - Bauer, Jéssica Mariela; Souza, Marianne Cásseres de; Saueressig, Gislaine Gabriele; Lcchese, Juliane; Sellitto, Miguel Afonso (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2015)
This article aims to describe how tires can return to the business cycle after their use. The research method adopted was the double case study. In the first case it was verified a company of collection and sorting of waste tire and rubber (TR1) and a cement plant that coprocesses tires in cement kilns (CM1) while the second case involved a waste tire collection and sorting company and rubber (TR2). It is concluded from this study that used tires can return to the business cycle in different ways and that there isn’t a single return channel. Tires may return as usable when they have yet driving conditions, demading some small repairs to be made, such as retreading, retreading and remoulding, and it was concluded that mostly these are intended for remoulding. And they can return as scrap destined for co-processing in cement kilns as a raw material for the cement industry, being crushed and mixed with other wastes, such as rice husk and lees or fossil fuels such as coal and petroleum coke or they can be recycled and be used for industry artifacts, construction, road construction industry and for friction materials.